Chapter 26 Whose Transition? A Review of Citizen Participation in the Energy System - Dunphy, Niall P. (Taylor & Francis, 2023)
Writing in the late 1980s, Jon Fiske describes reality as "always encoded [and most especially] by the codes of our culture". The energy transition is one of the latest sets of realities that comes with its own encoded messaging and nomenclatures. Citizens are increasingly expected to actively participate in the energy domain and play their part in transitioning to low-carbon energy systems. Terms like "energy citizen" have been used to describe (the accepted forms of) this participation, typically in quite prescriptive and rather limited roles, such as active consumer and prosumer. However, as with other manifestations of citizen-consumer ideals, where the framing is presented as the embodiment of freedom, the vagueness of such terms lock citizens out of what could potentially be a transformative conceptualization for transitioning to more equitable and empowering energy experiences. This chapter will examine how under-theorized and contested concepts like the "energy citizen" are already framing our collective experience(s) of the energy transition and asks for whom is the emerging energy system designed?